Can Website quality Moderate the Relationship between Information-task-fit and Electronic word of mouth? - Tarkang, MaryMagdaline Enow Mbi; Ozturen, Ali; Alola, Uju Violet (Wiley, 2022)
Information technology expertise has comprehensively revamped and made well recognized, the hospitality and tourism industry. Electronic businesses, which are different type of commercial business was constructed and established with the help of the internet, and this now affects the way clients react. The current research seeks to explore the effect of information-task-fit, on electronic word of mouth (eWOM) of users of Turkish airlines. Furthermore, the present study examines the moderating role of website quality on the aforementioned relationship. Six hundred and four usable questionnaires were obtained online within a 6 month period with the use of Google forms The current study used a quantitative and cross-sectional type of research method. The anticipated interactions were estimated using structural equation modeling. All anticipated relationships were supported, with discernment that the availability of users required information on the website impacted them to engage in eWOM. As hypothesized, the quality of the website, moderated the relationship between information-task-fit (INTF) and eWOM. The consequences of the present research proposes comprehensions into maintaining and why not improving the website quality by making the website user friendly, so as to attract potential users and keep current users. This study's complete model is scare in the airline service literature. In consequence there should be an added research on the influence of information task fit website information and design on supposed service quality and internet word of mouth. Managers should also uphold an elevation website ethics by employing good professional website builders to attract their usage. This study offers inferences for airline website quality.
Keywords: Purchase Intention; Supervisor Incivility; Online Purchase; Tourism; Impact; Hospitality; Design; Trust